PENGOLAHAN AIR HUJAN SEBAGAI PRODUK AIR BERSIH ALTERNATIF DENGAN TEKNOLOGI PENYARINGAN AIR SEDERHANA - Tarigan, J.; Sitepu, E.; Simanjuntak, C. (Buletin Udayana Mengabdi; Vol 24 No 4 (2025): Buletin Udayana Mengabdi, 2024)
High rainfall in Medan is a very good potential that must be utilized. The utilization of rainwater into clean water at HKBP Sidorame Medan Private High School is a breakthrough in the application of the green construction concept. This dedication is motivated by a lack of understanding about the conversion of rainwater into clean water which has an impact on lowering the operational costs of clean water which is still being distributed to schools by clean water service providers. The technique is a direct water filtration system that combines slow and fast sand filters. The collected rainwater is analyzed in the laboratory according to the Regulation of the Minister of Health of the Republic of Indonesia Number 32. Keywords: clean water, slow sand filter, fast sand filter, simple water filtration technology